Web scraping of food retail prices: An analysis of internet food retail sales prices - Jens-Peter Loy; Yanjun Ren (Künstliche Intelligenz in der Agrar- und Ernährungswirtschaft, 42. GIL-Jahrestagung, Tänikon, Ettenhausen, 21.-22.02.2022, 2022)
In this paper, we develop a theory of food retail promotional strategy. We test the theory using online food retail prices. A python code is applied to retrieve information from the web page mytime.de. Mytime.de is an online grocery outlet that belongs to the Bünting Group, a food retailer in North-West Germany. The promotional sales on mytime.de show a complementary relationship between breadth and depth of sales, indicating that in order to attract consumers, stores raise both the number (breadth) and the depth of price promotions.
Keywords: 330; e-food retailing; promotional sales; Germany